Tinjauan Hadits Dan Perspektif Ulama Terkait Membaca Do’a Ketika Berhubungan Seksual - Ana Nor Laily (PT. Sharia Journal and Education Center, 2024)
Abstract This research reviews the importance of reading basmallah and prayers during sexual intercourse. This research aims to find out how the hadith regulates the manners and ethics of sexual relations that educate husbands and wives in carrying out sexual relations. This research uses empirical research methods, using data collection techniques, namely literature studies that examine literature reviews, journals and hadiths that examine etiquette and ethics in sexual relations and the wisdom contained in etiquette and ethics in sexual relations. This research can be concluded that etiquette when engaging in sexual intercourse has a priority, including avoiding being disturbed by demons during sexual intercourse. And children who are the result of sexual relations are protected from demonic interference. Keywords: Manners And Ethics, husband and wife, pray Abstrak Penelitian ini meninjau pentingnya membaca basmallah dan do’a saat melakukan hubungan seksual. Penelitian ini bertujuan untuk mengetahui bagaimana hadits mengatur adab dan etika berhubungan seksual yang mengedukasi para suami dan istri dalam melakukan hubungan seksual. Penelitian ini menggunakan metode penelitian empiris, dengan menggunakan teknik pengumpulan data yaitu studi pustaka yang menelaah literature review, jurnal dan hadits yang menelaah tentang adab dan etika dalam berhubungan seksual dan hikmah yang terkandung dalam adab dan etika berhubungan seksual. Penelitian ini dapat disimpulkan bahwa adab saat melakukan hubungan seksual memliki keutamaan diantaranya agar tidak diganggu setan saat melakukan hubungan seksual tersebut. Dan anak yang menjadi hasil dari hubungan seksual tersebut dilindungi dari gangguan setan. Kata kunci: Adab dan etika, Suami Istri, Do’a